Prevalence of musculoskeletal problems in laboratory technicians - López-González, Mª Jesús; González Menéndez, Silvia; González-Menéndez, Eva (International Journal of Occupational Safety and Ergonomics, 2022)
Purpose. The aim of this work was to analyze the prevalence of work-related musculoskeletal symptoms in laboratory technicians and their relation to personal and organizational factors, as well as the lack of specific training on work-related risks. Methods. A standardized Nordic questionnaire made for the Spanish population and a survey of sociodemographic variables and organizational aspects were applied to a sample of 460 Spanish laboratory technicians. The statistical analysis was done through R version 3.4.3. Results. Of the sample studied, 84.5% presented some musculoskeletal discomfort, with a higher percentage in women. The probability of having discomfort was eight times higher for those older than 46 years and the most affected part of the body was the neck. The variables that were associated more significantly with the probability to suffer discomfort in the most affected parts of the body (neck, right shoulder and right wrist) were gender, education level, prevention knowledge and seniority. Conclusions. It is necessary to implement plans to train in specific risks according to the activities done by these professionals. © 2019 Central Institute for Labour Protection–National Research Institute (CIOP-PIB).
Keywords: ergonomics; laboratory technicians; musculoskeletal disorders; prevalence; standardized Nordic musculoskeletal questionnaire; Scopus; JCR